Inuit Attitudes towards Co-Managing Wildlife in Three Communities in the Kivalliq Region of Nunavut, Canada - Lokken, Nils A.A.; Clark, Douglas A.; Broderstad, Else G.; Hausner, Vera H. (ARCTIC, 2019)
We explored Inuit attitudes towards co-managing wildlife in the Kivalliq Region of Nunavut, Canada, working in partnership with the hunters and trappers’ organizations of Igluligaarjuk (Chesterfield Inlet), Tikirarjuaq (Whale Cove), and Qamani’tuaq (Baker Lake). In mixed-methods interviews, study participants in the two coastal communities described dissatisfaction with polar bear (Ursus maritimus) management outcomes, in contrast to a general satisfaction with (or indifference to) the management of other species. Interviewees expressed concern about grizzly bear (Ursus arctos) and, more prominently, caribou (Rangifer tarandus groenlandicus) populations in Qamani’tuaq, the inland community. Researchers have predicted that conflicts specific to polar bear management could lead to regulations being ignored or even defied and endanger the entire system of wildlife co-management. Our results indicate that dissatisfaction over decisions is specific to polar bear management outcomes and does not necessarily apply to the broader system of wildlife co-management. The results suggest that the Nunavut wildlife co-management system is quite functional: polar bear issues aside, Inuit in Qamani’tuaq, Tikirarjuaq, and Igluligaarjuk are largely content with the current functioning of the wildlife co-management regime. Nous avons étudié les attitudes des Inuits à l’égard de la cogestion de la faune dans la région de Kivalliq, au Nunavut, Canada, en collaboration avec les organisations de chasseurs et de trappeurs d’Igluligaarjuk (inlet Chesterfield), de Tikirarjuaq (Whale Cove) et de Qamani’tuaq (Baker Lake). Dans le cadre d’entretiens effectués au moyen de diverses méthodes, les participants à l’étude des deux collectivités côtières ont exprimé leur mécontentement à l’égard des résultats de la gestion de l’ours polaire (Ursus maritimus), comparativement à leur satisfaction générale (ou à leur indifférence) quant à la gestion des autres espèces. Par ailleurs, les personnes interrogées ont exprimé des inquiétudes par rapport ...